Pemodelan Stunting pada Balita di Indonesia Menggunakan Geographically Weighted Regression (GWR) - Sari, Rida Purnama; Winanda, Rara Sandhy (Journal of Mathematics UNP, 2023)
Stunting affects children's growth, with the number of cases of stunting under five in Indonesia amounting to 21.6 percent in 2022. Each province in Indonesia has different stunting rates. So a solution is needed to find out the right factors as a form of prevention of cases of stunting toddlers. This study uses geographically weighted regression in modeling the stunting rate, with variables that are assumed to influence it. Based on the spatial heterogeneity test, the stunting rate among toddlers varies in each region. Furthermore, several regional groups were formed based on significant variables. The first group is provinces that do not have explanatory variables that affect stunting rates in children under five. Meanwhile, the second group showed Low Birth Weight (LBW) as an influencing variable and the third group consisted of exclusive breastfeeding and Low Birth Weight (LBW) as a variable affecting stunting rates in toddlers.